Stability analysis of solid state lasers regarding thermal lensing effect - Graupeter, Thomas; Pflaum, Christoph (Laser Sources and Applications, 2012)
The stability of solid-state lasers is influenced by the thermal lensing effect in the crystal. This effect is based on the deformation of the end faces of the crystal and the temperature dependence of the refraction index. It also depends on the photoelastic effect produced by thermal induced stress in the crystal. The analysis of the photoelastic effect is important for high power lasers and for lasers with a radially polarized laser beam. In this work, we use FE model to calculate the deformation, heat and stress distribution in the laser crystal with high accuracy. We also simulated the refraction index anisotropy with respect to the crystal orientation using the calculated stress distribution. As a result of our simulation, we can study stability of laser resonators for both radially and azimuthally polarized laser beam. © 2012 SPIE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.lsinfs.stabil
Keywords: Laser; Photoelastic effect; Refraction index; Stability; Thermal lensing; YAG